Distinct Coagulopathy With Myocardial Injury and Pulmonary Embolism in COVID-19 - Ayman R. Fath MD; Amro Aglan MBChB; Kyle S. Varkoly BS; Abdullah S. Eldaly MBChB; Roxana N. Beladi BA; Arnold Forlemu MD; Nawfal Mihyawi MD; Anup Solsi MD; Sharjeel Israr MD; Alexandra R. Lucas MD, FRCP (SAGE Publishing, 2021)
In this article, we report a case of a 61-year-old male who was diagnosed with SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2), presenting with acute respiratory distress syndrome requiring intubation and hemodynamic support, marked D-Dimer and troponin I elevation, worsening ST-elevation myocardial infarction on repeat electrocardiograms, and a negative coronary angiogram ruling out a coronary artery thrombosis or occlusion. With worsening diffuse ST-segment elevation on electrocardiograms and reduced ejection fraction on echocardiography in the setting of systemic inflammation, fulminant myocarditis was highly suspected. Despite optimal medical treatment, the patient's condition deteriorated and was complicated by cardiac arrest that failed resuscitation. Although myocarditis was initially suspected, the autopsy revealed no evidence of myocarditis or pericarditis but did demonstrate multiple microscopic sites of myocardial ischemia together with thrombi in the left atrium and pulmonary vasculature. Additionally, scattered microscopic cardiomyocyte necrosis with pathological diagnosis of small vessel micro-thrombotic occlusions. These findings are potentially exacerbated by inflammation-induced coagulopathy, hypoxia, hypotension, and stress, that is, a multifactorial etiology. Further research and an improved understanding are needed to define the precise pathophysiology of the coagulopathic state causing widespread micro-thrombosis with subsequent myocardial and pulmonary injury.